SISTEM INFORMASI GEOGRAFIS PEMETAAN FASILITAS KESEHATAN BPJS DI KABUPATEN JEPARA DENGAN ALGORITMA DIJKSTRA BERBASIS WEB - Musyarraf, Fajrul Fahry; Sarwido, Sarwido; Kusumodestoni, R. Hadapiningradja (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
Mapping BPJS health facilities in Jepara Regency is an important step to improve health accessibility. To support this effort, a web-based geographic information system was developed that is designed to map BPJS health facilities and determine the shortest route using Dijkstra's algorithm. This application was built with the Laravel 9 PHP framework and utilizes Leaflet for interactive map display. The results show that this system is effective in presenting complete information about BPJS health facilities in Jepara Regency. The main feature of this application is its ability to calculate and display the shortest route from the user's location to the selected health facility using Dijkstra's algorithm. With this feature, users can easily find the fastest path to the health facility, thus improving the efficiency and accessibility of health care in the region